Recognition Regimes for Religious Minorities in Europe: Institutional Change and Reproduction - Hofhansel, Claus (A journal of church and state, 2015)
Increasing religious pluralism has forced European governments to confront demands for the recognition of religious differences. Setting aside a section of a ce